How organizational culture affects newcomers' motivation in China--A comparative study of a state-owned and a private company - Zhou, Ting (2009)
This study seeks to explore the relationship between work motivation and organizational culture. It is a mini case study conducted in China aiming at investigating how organizational culture affects newcomers’ work motivation. The research was designed as a comparative study in a state-owned and a private company which are main parts in China so as to examine how different organizational culture types leads to dissimilar work motivation. Newcomers who are relatively low organizational socialization were involved in these two organizations. Hence, organizational socialization was examined as an important variable. 21 questionnaires and 19 interviews were conducted together to collect primary data in case organizations. The result of the research has shown that organizational culture affects newcomers’ work motivation by influencing individual organizational socialization largely. Newcomers identified different types of information they need and decided diverse informal individual socialization approaches to seek such information during socialization process under different organizational cultures.